Intrazerebrale Blutungen unter oraler Antikoagulation - Beynon, Christopher; Unterberg, Andreas (Medizinische Klinik, Intensivmedizin und Notfallmedizin, 2017)
Intracerebral haemorrhage during treatment with oral anticoagulants is associated with high rates of morbidity and mortality. Impaired haemostasis can lead to progressive haematomas and, therefore, it should be identified early in order to initiate measures to reverse anticoagulation. Substitution of coagulation factors is essential in the treatment of these patients, but other intensive care measures such as blood pressure control are mandatory as well.